PERSEPSI GURU TERHADAP PENGARUH SUVERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMP NEGERI KECAMATAN CIMERAK KABUPATEN PANGANDARAN - Nurmalasari, Neneng (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
This article aims to determine the effect of supervision of Head master toward teacher performance, determine the influence of teacher work motivation toward teacher performance, and determine the influence of Head master supervision and teacher’s work motivation classically toward teacher performance. The method used is descriptive analysis method. It will hopefully be able to understand the problem based on the phenomenon at the time of the study. The subjects of this study were 120 State Teachers in Cimerak Subdistrict, Pangandaran Regency, with a total sample of 75 teachers. While the object of this study is the supervision of the principal, work motivation of teachers, and teacher performance. The data collected in this study were captured through a questionnaire in the form of scales in the range of scores from 1 to 5. The result of research is : 1) the effect of school principal supervision (X1) on Teacher Performance (Y) of 0.091; 2) the effect of teacher work motivation (X2) on teacher performance (Y) of 0.139; and 3) the influence of school principal supervision (X1) and teacher work motivation (X2) on teacher performance (Y) together by 0.165, meaning 0.835 is the influence of factors other than those examined.